Comprehensive Review of Analytical Approaches for the Detection of Diphenhydramine: A Systematic Analysis - Alphonsa Tom; Tina Sharma; Mahipal Singh Sankhla; Archana Gautam (Journal of Forensic Science and Medicine)
Diphenhydramine (DPH), a commonly used over-the-counter (OTC) antihistamine and sedative, requires accurate and reliable analytical methods to be evaluated in various matrices. The systematic review provides a comprehensive analysis of the current analytical techniques to detect DPH in biological samples and pharmaceutical formulations between 2012 and 2022. Case reports of DPH-related fatalities and intoxications were included along with crime statistics of OTC drug seizure in India from 2017 to 2021. The review also points out gaps in the body of knowledge and recommends areas for future study to provide novel and reliable analytical techniques for detecting DPH. Researchers, analysts, and regulatory bodies engaged in toxicology, drug analysis, and pharmaceutical quality control will find this review’s conclusions helpful.